B chromosome variants in Prochilodus lineatus (Characiformes, Prochilodontidae) analyzed by microdissection and chromosome painting techniques. Issue 2 (2nd April 2016) - Penitente, Manolo; Daniel, Sandro Natal; Scudeler, Patrícia Elda Sobrinho; Foresti, Fausto; Porto-Foresti, Fábio
Abstract: Several cytogenetic studies in Prochilodus lineatus (Valenciennes 1836) describe a striking system of supernumerary microchromosomes revealing the occurrence of three morphological types visualized as acrocentric, metacentric and submetacentric. The present study aimed to compare the DNA homology among the B chromosome variants, as well as the components of the standard complement using total B specific probes obtained by microdissection. This technique, which allows direct isolation of DNA from each B chromosome variant of interest, was applied to obtain the probes. Accordingly, cross hybridizations targeting all types were performed by using the fluorescence in situ hybridization technique. The results obtained revealed signals of hybridization on all kinds of B chromosomes, indicating homology among the variants. Moreover, markings on the standard A complement were observed using the B submetacentric chromosome specific probe. Based on these data, we can infer that B chromosome variants in P. lineatus have homologous regions, suggesting a common origin from an ancestral variant. Furthermore, it can be also hypothesized that the primitive supernumerary was probably originated from elements of the standard complement, since the B submetacentric morphotype shares sequences with the centromeric region of some chromosomes of the A complement.